Gender Stereotypes, Maternity and Employment: A Psychosociological Analysis - Garrido Luque, Alicia; Álvaro Estramiana, José Luis; Rosas Torres, Ana Raquel (Pensando Psicología, 2018)
Introduction: In the last decades there has been a substantial change in the position of women in the labor market, although it cannot yet be said that there is an equal share of jobs between men and women. On the one hand, there are still clear indications of employment discrimination against women and, on the other hand, the participation of men in domestic work has not grown at the same rate as that of women in paid work.Objective: To reflect on the ideological bases supporting this inequality by analyzing the weight that traditional gender stereotypes, especially those built around motherhood, have on the career of young women.Method: Data come from a qualitative study in which a sample of young people with different positions within the labor market was interviewed.Results: Generally, the discourses on maternity and upbringing are characterized by a marked biological and psychological essentialism that attributes a greater natural capacity for the care of children to women.Conclusions: Gender stereotypes that are built around motherhood are one of the main ideological factors that maintain discrimination against women in the labor market.
Keywords: gender stereotypes; labor exclusion; motherhood; fatherhood; work time